AGREEMENT BETWEEN CLINICAL FEATURES OF SCIATICA AND 3.0T MAGNETIC RESONANCE IMAGING FINDINGS - Saman Mubashar; Tasmia Mudassar; Beenish Bajwa; Mudassar Ahmed Bajwa; Mubashar Ahmed Bajwa; Aemen Shafqat Bazaz (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To determine agreement between clinical features of sciatica and 3.0 T magnetic resonance imaging findings.